(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Strategies for achieving maximum service in a library can be done with the use of the library. Library as a source of information is expected not only to serve the public to obtain information, but it can maintain its existence as an information service institution that develops with the progress of information technology. The purpose of research to gather and analyze the utilization of the library in Badan Perpustakaan, Arsip dan Dokumentasi Provinsi Sulawesi Utara. The methodology used is qualitative, data were collected through observation, interviews and literature study. The number of informants 14 people. The data obtained were related to the utilization of the library which were then analyzed through categorization and data reduction. The result of this study shows that in the Library Utilization Badan Perpustakaan, Arsip dan Dokumentasi Provinsi Sulawesi Utara it is not going well. Existing human resources quality of work is still very low. The lack of mastery of information technology and the slow pace in providing services librarian. State library collection is irrelevant, Means still manual information retrieval, yet has the facilities, such as internet and OPAC, covered services system has not gone well. Conclusion is that the utilization of the library in Badan Perpustakaan, Arsip dan Dokumentasi Provinsi Sulawesi Utara have not been going well, human resources are still lacking quality work, which is not relevant collections, facilities and infrastructure are still lacking and closed the service system has not gone well. So that should make improvements human resources through education and training levels. Increasing the number of employees in particular librarian library educational background. Procure to increase the number of library collections. Adding a means of tracking information such as OPAC and the Internet. Fixing system covered services for smooth service information. Key words : Library Reforms, Human Resources, Collection, Fasilities and Infrastrukture, System Service